Pregnancy Outcomes in Women With Rheumatoid Arthritis: A Systematic Review and Meta-analysis. Issue 1 (January 2023) - Sim, Bernice L.; Daniel, Rohan Suresh; Hong, Sam S.; Matar, Reem H.; Ganiel, Imri; Nakanishi, Hayato; Mansour, Rania; Than, Christian A.; Alrahmani, Layan
Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory rheumatic disease affecting multiple joints and can also be a systemic widespread, affecting major organs. Rheumatoid arthritis is associated with greater adverse maternal and neonatal outcomes in comparison to the general obstetric population. This systematic review and meta-analysis aims to investigate the pregnancy outcomes in RA patients in comparison to the general pregnant population. Nine studies involving 11, 999 RA patients met the eligibility criteria with 9, 921, 808 controls. Rheumatoid arthritis patients were compared with their control counterparts according to random-effects model statistical analysis. We searched databases from inception to September 8, 2021. Eligible studies reported maternal outcomes (preeclampsia, cesarean delivery, and preterm delivery) and/or neonatal outcomes. Data were pooled across using random-effects model. Subgroup analysis was conducted on RA patients alone. The review was registered prospectively with PROSPERO (CRD42021250521). In terms of maternal outcomes, there was an increased rate of cesarean delivery (odds ratio [OR], 1.55), preeclampsia (OR, 1.61), and preterm delivery (OR, 1.83) in RA patients compared with their control counterparts. In terms of neonatal outcomes, a higher rate of lower gestational weight (mean difference [MD], −0.19 kg), requirement for neonate intensive care unit admission (OR, 1.34), and stillbirths (OR, 1.99) were observed in RA patients compared with the controls. A subgroup analysis of 4 studies involving only RA patients (n = 3761) was conducted. A total of 33.2% of patients had a cesarean delivery, 7.3% had preeclampsia, 14.8% had a preterm delivery, and 9.5% of neonates had low birth weight. Compared with the general pregnant population, women with RA tend to have a higher risk of maternal and neonatal complications. As a result, this study hopes to increase awareness into the importance of counseling and managing RA patients.